Best Answer

Not neatly. Applying the quadratic formula, we find two real solutions: -1 plus or minus the square root of three.

x = 0.7320508075688772

x = -2.7320508075688772

Q: Can x2 plus 2x-2 be factored?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

Dividing all terms by 2 gives: x2+9x+18 = (x+3)(x+6) when factored

Divide all terms by 2 it is then x2-15+56 = (x-7)(x-8) when factored

6x3 - x2 + 17 = 2x2 + 47 6x3 - x2 - 2x2 = 47 - 17 x2(6x - 1 - 2) = 30 this is the simplest factorisation.

x2 + 7x = 2x2 + 6 x2 - 2x2 + 7x = 6 -x2 +7x - 6 = 0 or alternatively x2 - 7x + 6 = 0

x3 - x2 + 2x = x*(x2 - x + 2) which cannot be factored further.

Related questions

x2 + x2 = 2x2

x2 + x2 = 2x2

Dividing all terms by 2 gives: x2+9x+18 = (x+3)(x+6) when factored

Divide all terms by 2 it is then x2-15+56 = (x-7)(x-8) when factored

6x3 - x2 + 17 = 2x2 + 47 6x3 - x2 - 2x2 = 47 - 17 x2(6x - 1 - 2) = 30 this is the simplest factorisation.

2x2 + 3x + 1 = (x + 1)(2x + 1)

x3 - x2 + 2x = x*(x2 - x + 2) which cannot be factored further.

x2 + 7x = 2x2 + 6 x2 - 2x2 + 7x = 6 -x2 +7x - 6 = 0 or alternatively x2 - 7x + 6 = 0

2x2 + x2 = 3x2

x2+x-6 = (x-2)(x+3) when factored

x2 + 1 can't be factored in the real numbers. If complex numbers are acceptable, it can be factored as (x + i)(x - i).

2x2+5x+3 = (2x+3)(x+1) when factored